An intriguing case of episodic hypersomnolence- Kleine–Levin syndrome, a diagnosis often missed - Shreya Chauhan; Ramakant K Sabharwal; Praveen Kumar; Paramita Paul (Current Medicine Research and Practice, 2023)
A sleep disorder is characterised by alteration in normal pattern of sleep enough to interfere with the normal functioning of an individual. Sleep disorders are broadly classified as primary sleep disorders such as dyssomnias, hypersomnia and parasomnias and secondary due to medical and mental disorders such as anxiety or substance abuse. We report the case of a 12-year-old boy who presented to us with episodic hypersomnolence, hyperphagia and behavioural abnormalities and was initially managed as epilepsy at another hospital. He was subsequently diagnosed as primary sleep disorder, Kleine–Levin syndrome. We also describe the diagnostic approach to such a case and the crucial role of functional brain imaging in it.